2015
DOI: 10.2147/ppa.s85773
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported treatment satisfaction and choice of dosing frequency with biologic treatment for moderate to severe plaque psoriasis

Abstract: BackgroundModerate to severe plaque psoriasis has a serious effect on health-related quality of life. Patients treated with biologic medications place importance on satisfaction and treatment frequency options. We assessed patient-reported treatment satisfaction and dosing frequency choice with biologics.MethodsWe used a health care claims database to identify patients with moderate to severe plaque psoriasis. Participants completed the Treatment Satisfaction Questionnaire for Medication. Results were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Appropriate dose selection is a critical issue during drug development and must balance key considerations including efficacy, safety and convenience . If the dose is inadequate, dose escalation may be necessary .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriate dose selection is a critical issue during drug development and must balance key considerations including efficacy, safety and convenience . If the dose is inadequate, dose escalation may be necessary .…”
Section: Discussionmentioning
confidence: 99%
“…16,21 Appropriate dose selection is a critical issue during drug development and must balance key considerations including efficacy, safety and convenience. 22,23 If the dose is inadequate, dose escalation may be necessary. 24,25 With the data presented here, and additional population PK modelling and exposure-response modelling analyses outlined above, as well as the comprehensive efficacy and safety assessments in Phase 3, the method for dose selection in the guselkumab psoriasis programme was robust and yielded the optimal, convenient dosing regimen of 100 mg at weeks 0, 4, then q8w for the broader population of moderate-to-severe psoriasis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although dermatologists involved into this study think that a good formulation as well as an easy‐to‐apply regimen add to adherence, they primarily focus on patient's individual clinical aspects when selecting the medication to be prescribed (i.e. significant findings on the skin, presence of lesions in visible body areas, presence of joint pain, presence of disturbing pruritus) as well as on the expected efficacy of the medication as discontinuation of biologics seems often to be linked to treatment inefficacy .…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the shorter interval between injections of etanercept (once or twice weekly) than for adalimumab (every 4th week) or ustekinumab (every 12th week) is of importance. It has been shown that longer intervals (every 2nd or 3rd month) are more preferable to the patients than more frequent injections [26]. Indeed, in the MARS questionnaire surveying the attitudes to treatment, the significant difference between etanercept and the other two biologics was captured by questions Q2, Q4, and Q6, which are related to the ease of administration of the medicine (fig.…”
Section: Discussionmentioning
confidence: 99%